Embedded Agency in Institutional Theory: Problem or Paradox? - Lok, Jaco; Willmott, Hugh (Academy of Management Review, 2019)
In “Beyond Constraining and Enabling: Toward New Microfoundations in Institutional Theory” Professor Cardinale (2018) seeks to expose and correct “shortcomings” (p.133) in institutional theory’s conceptualization of structure, agency and their relationship. To this end, he theorizes the “different mechanism[s] through which actors are embedded in structure” (p.134). We agree that institutional theory’s microfoundations merit theoretical attention and development. However, we question the premise that the issue of agency in institutional theory is adequately, or even plausibly, formulated as one of “embeddedness”. We also challenge the relevance of Professor Cardinale’s engagement of Husserl to help solve what we argue to be a phantom problem central to his theory.